The execution premium : linking strategy to operations for competitive advantage - Kaplan, Robert S.; Norton, David P., 1941- ([Boston, Massachusetts] : Harvard Business Press, 2008)
In a world of stiffening competition, business strategy is more crucial than ever. Yet most organizations struggle in this area--not with formulating strategy but with executing it, or putting their strategy into action. Owing to execution failures, companies realize just a fraction of the financial performance promised in their strategic plans. It doesn't have to be that way, maintain Robert Kaplan and David Norton in The Execution Premium. Building on their breakthrough works on strategy-focused organizations, the authors describe a multistage system that enables you to gain measurable benefits from your carefully formulated business strategy. This book shows you how to: Develop an effective strategy--with tools such as SWOT analysis, vision formulation, and strategic change agendas Plan execution of the strategy--through portfolios of strategic initiatives linked to strategy maps and Balanced Scorecards Put your strategy into action--by integrating operational tools such as process dashboards, rolling forecasts, and activity-based costing Test and update your strategy--using carefully designed management meetings to review operational and strategic data. Drawing on extensive research and detailed case studies from a broad array of industries, The Execution Premium presents a systematic and proven framework for achieving the financial results promised by your strategy.
Introduction -- Develop the strategy -- Plan the strategy -- Strategic initiatives : launching the strategy into motion -- Aligning organizational units and employees -- Plan operations : align process improvement programs -- Plan operations : sales forecasts, resource capacity and dynamic budgets -- Operational and strategy review meetings -- Meetings to test and adapt the strategy -- The office of strategy management
Includes bibliographical references
Robert S. Kaplan is the Baker Foundation Professor at the Harvard Business School. He has been a codeveloper of both activity-based costing and the Balanced Scorecard. David P. Norton is a founder and director of the Palladium Group, a consultancy focusing on strategy execution, and is codeveloper of the Balanced Scorecard.
online resource; title from epub cover (ProQuest Ebook Central, viewed May 4, 2021)
Master record variable field(s) change: 050
Keywords: Strategic planning; Business planning; Organizational effectiveness; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Strategic planning; Business planning; Organizational effectiveness; Business planning; Organizational effectiveness; Strategic planning; Planification stratégique; elektronické knihy; electronic books